Spatial diversity and distribution of fern and lycophyte species in karst and non-karst landscapes towards conservation needs - delos Angeles, Marjorie D.; Radbouchoom, Sirilak; Ngarega, Boniface K.; Lapuz, R. Sedricke; Schneider, Harald (Frontiers in Plant Science, 2025)
Karst formations are distinguished by their high levels of species diversity and endemism, including ferns and lycophytes. However, the existing data on plant community composition in karst formations remains deficient. Addressing these knowledge gaps is imperative, given the current accelerated rates of species loss, to enhance efforts to conserve biodiversity in these habitats. This study documents and explains patterns of fern and lycophyte species diversity within karst landscapes (KL) and non-karst landscapes (NKL) in the Philippines. Our comprehensive analysis involved aggregating 19,529 occurrence points encompassing 1,024 fern and lycophyte species sourced from field expeditions, voucher records from local herbaria, and online databases. Indices for species richness, weighted endemism, and corrected weighted endemism were then computed across KL and NKL areas to describe spatial diversity and identify fern and lycophyte hotspot areas. Gap analyses were also performed to determine if established protected areas (PAs) were sufficient to cover the identified fern and lycophyte diversity hotspots. Principal Component Analysis (PCA) was conducted to determine potential ecological drivers of distribution between KL and NKL areas. The findings reveal that most fern and lycophyte species were recorded to occur in NKL areas, with 995 (97.16%) species identified, while 676 (66.02%) species were documented to occur in KLs, including 29 (2.83%) exclusive to karsts. Identified hotspots for NKL are within mountain ecosystems, which are already under existing legal protection. In contrast, KLs have five areas identified as congruent hotspots but considered gap areas due to their exclusion from current PA boundaries. Existing PAs thus provide less protection to karst habitats and their associated floras. PCA did not reveal any significant environmental predictors, suggesting separation of KL and NKL species distributions, possibly due to lack of high-resolution environment data available for karsts. To facilitate the conservation of fern and lycophyte species in karsts, we propose installing and expanding existing PA boundaries, along with conducting more focused surveys in karst regions to better understand their ecological dynamics.